Highly Potent 1H-1,2,3-Triazole-Tethered Isatin-Metronidazole Conjugates Against Anaerobic Foodborne, Waterborne, and Sexually-Transmitted Protozoal Parasites - Kumar, Sumit; Bains, Trpta; Won Kim, Ashley Sae; Tam, Christina; Kim, Jong; Cheng, Luisa W.; Land, Kirkwood M.; Debnath, Anjan; Kumar, Vipan (Frontiers in Cellular and Infection Microbiology, 2018)
Parasitic infections like amebiasis, trichomoniasis, and giardiasis are major health threats with their widespread harmful consequences in tropical and subtropical regions of the world. FDA approved various types of nitro-imidazoles such as ornidazole, benznidazole and secnidazole are widely used medications against anaerobic infections but have lower efficacies than metronidazole (MTZ). MTZ is the current drug of choice for amebiasis, giardiasis and trichomoniasis but it has several adverse effects and potential resistance is a concern. In order to develop alternative antimicrobials, a library of 1H-1,2,3-triazole-tethered metronidazole-isatin conjugates has been synthesized using Huisgen’s azide-alkyne cycloaddition reaction and evaluated for their amebicidal, anti-trichomonal and anti-giardial potential. Most of the synthesized conjugates exhibited comparable activities with that of the standard drug MTZ against Trichomonas vaginalis and Tritrichomonas foetus while better activities were observed against Entamoeba histolytica and Giardia lamblia. Conjugates 9d and 10a were found to be 2-3 folds more potent than MTZ against E. histolytica and 8-16 folds more potent than MTZ against G. lamblia. Further analysis of these compounds on fungi and bacteria did not show inhibitory activity, demonstrating their specific anti-protozoal properties.